Analisis Prediksi Kebangkrutan dan Rasio Keuangan Bank Umum Syariah dengan Metode Altman Z-Score pada Tahun 2011-2015 - Rais Sani Muharrami; Sinta Sinta (Universitas Ahmad Dahlan, 2018)
The purpose of this research is to perform a comparative analysis of bankruptcy prediction and financial ratio related to Bank Umum Syariah Devisa and Bank Umum Syariah non Devisa. This research applied Altman model on Bank Umum Syariah Devisa and Bank Umum Syariah non Devisa to explain its bankruptcy prediction., while Mann Withney test is used to show a comparative analysis on its financial ratio related to bankruptcy.Â Data was use in this research is time series data, the data from 2011 up to 2015. The data is obtained from publication in Otoritas Jasa Keuangan (OJK) and publication in each bankâ€™s website. The sampling techniques using purposive sampling methods. This research can be concluding that there is no difference between Bank Umum Syariah Devisa and Bank Umum Syariah non Devisa on Bankruptcy prediction with Altman model. In financial ratios related to bankrupty exposure such as liquidity, Profitability, and Productivity has not significant difference to. While insolvency ratio at Bank Umum Syariah Devisa and Bank Umum Syariah non Devisa foundto have differences. For bankruptcy prediction at Bank Umum Syariah Devisa and Bank Umum Syariah non Devisa is found not difference. So, we can conclude that the difference in bankruptcy perdiction on Bank Umum Syariah Devisa and Bank Umum Syariah non Devisa caused by the absence of dirrerences in the financial ratios with regard to bankruptcy unless insolvency.